Sistem E-Learning Terintegrasi Web Sebagai Solusi Dalam Meningkatkan Kualitas Pendidikan Dan Pembelajaran Mahasiswa - Abdurrasyid Abdurrasyid; Indrianto Indrianto; Meilia Nur Indah Susanti (University of Muhammadiyah Tangerang, 2017)
Learning media is one fairly important part in the implementation of lectures, given the variety of obstacles and challenges that would be found during college. The role of instructional media is often overlooked, so that students not uncommon to feel tired and bored in a lecture which resulted in less than optimal results. Especially if the result of courses that only limited interaction in the classroom less use of media that actually existed even less than the maximum.Web design media applications E-learning is one solution, using a web-based Java and MySQL database in the making. And using SDLC approach in its implementation, and strengthened by the questionnaire in the process of making this application.Designing web application e-learning is intended to facilitate the process of actual lectures can be done anywhere and anytime with the data material and quiz subjects more safely and effectively stored in the application database.